César Bruto: incorrectness from a Homo typographicus - Cilento, Laura (Romanica Olomucensia, 2019)
César Bruto is a heteronym for Carlos Warnes, an Argentine writer and humorist who developed his career between 1935 and 1980. By 1942 his Cesar Bruto section in Cascabel magazine had become a massive attraction; this paper aims to understand its peculiar humoristic formula. In spite of the notorious incompetence of Bruto as a writer, in this paper the claim is made that this is only one of the dimensions of his humoristic success; the rest of them are based on the material conditions brought by the journalistic media as a device that intertwines with the literary text and propels the fictional contract that is assumed with the reader. The research is founded on the material conditions of the design of the magazine and on the analysis of the influence of the aesthetic programme. Openly staking a claim to experimentalism, Cascabel joined innovative ideas that impressed with their communication of humour and surprise. The main procedures found in the first two years of the magazine's life show an interest on trompe l'oeil and self-reference, so the magazine preserves a central place as a main enunciative focus and by this logic succeeded in introducing its main authors, as the case of Cesar Bruto shows with more consistency. In this peculiar mood, Cascabel is the indispensable launching base for Cesar Bruto's formula of literary humour grounded in massive support.
Keywords: humour; César Bruto; fictional contract; media; Cascabel magazine